The potential of PGPR and Trichoderma-based bioproducts and resistant cultivars as tools to manage clubroot disease in cruciferous crops - Moreno-Velandia, Carlos Andrés; Garcia-Arias, Francy Liliana; Dávila-Mora, Lorena; Rodríguez, Edwin; Villabona-Gélvez, Alejandro; Revelo-Gómez, Eliana Gisela; Marcillo-Paguay, Carlos Alberto; Riascos-Ortiz, Donald Heberth; Zuluaga, Andrea Paola (Frontiers in Plant Science, 2024)
The objective of this research was to determine the potential use of eco-friendly technologies to reduce the clubroot disease caused by Plasmodiophora brassicae, the main constraint of cruciferous crops worldwide. Two commercial bioproducts were evaluated in susceptible broccoli, one based on PGPR-consortium (Bacillus amyloliquefaciens, Bacillus pumilus and Agrobacterium radiobacter K84) and the other one based on Trichoderma koningiopsis Th003 (Tricotec® WG). Additionally, the resistant broccoli cv. Monclano was tested under two concentrations of resting spores (RS) of P. brassicae, 1x103 and 1x105 RS g-1 of soil. First phase of evaluations with broccoli was carried out under greenhouse, while susceptible broccoli, cauliflower, and red cabbage were included in a subsequent field phase. Tebuconazole + Trifloxystrobin mixture and Fluazinam were included as positive controls. The effectiveness of the bioproducts depended on the nature of the biocontrol agent, the concentration of P. brassicae, and the dose of treatment. Tricotec showed consistent plant growth promotion but no biocontrol effect against clubroot, and the rhizobacteria-based bioproduct significantly reduced the disease both in greenhouse and field experiments. Higher disease severity was observed with higher dose of Tricotec. Under field conditions, the rhizobacteria reduced the incidence progress by 26, 39, and 57% under high, medium, and low pressure of the pathogen, respectively. However, no reduction of clubroot severity under high pressure of the pathogen was observed. Complete inhibition of club formation in roots by the fungicide, but a phytotoxic effect was observed under greenhouse. Fungicides reduced the incidence progress of clubroot, but not the severity under high inoculum pressure in field. The fungicides, the bacterial treatment and the combination of bioproducts tended to delay the progress of the disease compared with the negative control and Tricotec alone. The resistant broccoli showed low level of disease under high concentration of P. brassicae (less than 10% incidence and up to 2% severity). These results suggested overall potential of commercial tools based on PGPR-consortium and plant resistance to control P. brassicae. The integration of control measures, the role of Trichoderma spp. in P. brassicae-cruciferous pathosystems and the need to recover highly infested soils will be discussed.